Keagungan Cinta dalam Puisi “Aku Ingin” karya Sapardi Djoko Damono: The Grandeur of Love in “Aku Ingin” Poem by Sapardi Djoko Damono - Sri Yono (Balai Bahasa Provinsi Papua, 2019)
In spite of the simplicity of his dictions, Sapardi Djoko Damono’s poems have deep meaning inside. It is becoming his peculiar features and extra ordinary esthetical achievement. This paper aims to analyze Sapardi Djoko Damono's “Aku Ingin” by using Riffaterre's semiotics structuralism. Through this method the message of the poem is becoming easier to be interpreted comprehensively. It is library research and the main data of this paper is “Aku Ingin” poem from his poem antology “Hujan Bulan Juni: Sepilihan Sajak” published by Gramedia Pustaka Utama. By reading the poem through Riffaterre's semiotics, heuristically and hermeneutically it is concluded that along with the simplicity of the dictions in “Aku Ingin” poem, they elaborate about grandeur love. It is sacred love that makes “Aku” has no willing to occupy anything and just gives the perfect sacrifice.